The effect of educational intervention based on BASNEF model for reducing internet addiction among female students: a quasi-experimental study - Batol Gholamian; Hossein Shahnazi; Akbar Hassanzadeh (BMC, 2019)
Abstract Background Adolescents and students are encountered with a challenge so-called "internet Addiction". This issue affects both their physical and mental health, as well as their academic, social, and family performance. The aim of the current research is to determine the impact of educational intervention. To achieve this aim, BASNEF is utilized to reduce the excessive use of the internet by students. Methods This quasi-experimental study was implemented on 120 high school female students in Shahrekord (west of Iran), which were addicted to the internet. Paticipants was randomly divided into two groups of control and intervention. For data collection before and after the intervention, the standard Yang internet Addiction Questionnaire and BASNEF researcher-developed Questionnaire were used. Educational intervention for mothers was conducted in one session (as the most important subjective norm) and for students in two sessions. This method was based on BASNEF construct. Then, data were analyzed using SPSS-20 and chi-square test, Mann-Whitney test, independent t-test, and paired t-test. Results After the education intervention, the mean scores of knowledge, attitude, subjective norms, perceived behavioral control and enabling factors in the intervention group were significantly different from the control group (p < 0.001). In Post-test assessment, the intervention group revealed a significant decrease, in terms of using the internet (based on the time). (p < 0.001). Conclusions The results of this study revealed that BASNEF and its related constructs was a suitable framework to design the educational interventions in order to reduce the extreme use of internet in students. Applying of this model can be a cognitive and intellectual framework that affects students' internet use behavior.